The impact of delivery profile of essential amino acids upon skeletal muscle protein synthesis in older men: clinical efficacy of pulse vs. bolus supply - Mitchell, W. Kyle; Phillips, Bethan E.; Williams, John P.; Rankin, Debbie; Lund, Jonathan N.; Wilkinson, Daniel J.; Smith, Kenneth; Atherton, Philip J. (American Physiological Society, 2015)
Essential amino acids (EAA) are responsible for skeletal muscle anabolic effects after nutrient intake. The pattern of appearance of EAA in blood, e.g., after intake of “slow” or “fast” protein sources or in response to grazing vs. bolus feeding patterns, may impact anabolism. However, the influence of this on muscle anabolism is poorly understood, particularly in older individuals. We determined the effects of divergent feeding profiles of EAA on blood flow, anabolic signaling, and muscle protein synthesis (MPS) in older men. Sixteen men (∼70 yr) consumed EAA either as a single dose (bolus, 15 g; n = 8) or as small repeated fractions (pulse, 4 × 3.75 g every 45 min; n = 8) during 13C6 phenylalanine infusion. Repeated blood samples and muscle biopsies permitted measurement of fasting and postprandial plasma EAA, insulin, anabolic signaling, and MPS. Muscle blood flow was assessed by contrast-enhanced ultrasound (Sonovue). Bolus achieved rapid insulinemia (12.7 μiU/ml 25-min postfeed), essential aminoacidemia (∼3,000 μM, 45–65 min postfeed), and mTORC1 activity; pulse achieved attenuated insulin responses, gradual low-amplitude aminoacidemia (∼1,800 μM 80–195 min after feeding), and undetectable mTORC1 signaling. Despite this, equivalent anabolic responses were observed: fasting FSRs of 0.051 and 0.047%/h (bolus and pulse, respectively) increased to 0.084 and 0.073%/h, respectively. Moreover, pulse led to sustainment of MPS beyond 180 min, when bolus MPS had returned to basal rates. We detected no benefit of rapid aminoacidemia in this older population despite enhanced anabolic signaling and greater overall EAA exposure. Rather, apparent delayed onset of the “muscle-full” effect permitted identical MPS following low-amplitude-sustained EAA exposure.